2019
DOI: 10.2169/internalmedicine.0920-18
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Alveolar Hemorrhaging with Hypertensive Emergency: A Rare but Important Cause of Hemoptysis

Abstract: Hypertensive emergency, which occurs even in young adults, induces systemic organ damage and results in a poor prognosis. We herein report the case of a 27-year-old man who developed alveolar hemorrhaging with hypertensive emergency. He presented with bloody sputum, renal failure, and extremely high blood pressure (200/128 mmHg). Chest computed tomography revealed diffuse bilateral alveolar infiltrates suggestive of diffuse alveolar hemorrhaging. After intensive therapy with anti-hypertensive drugs, the alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It is challenging to figure out a clear pathophysiological relationship between PPGLs and alveolar hemoptysis because the process that causes alveolar hemoptysis in people has not been fully identified [ 16 ]. Previous evidence [ 29 ] suggests that severe hypertension can precipitate the onset of alveolar bleeding. When catecholamines rise, they mostly act on α-adrenergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…It is challenging to figure out a clear pathophysiological relationship between PPGLs and alveolar hemoptysis because the process that causes alveolar hemoptysis in people has not been fully identified [ 16 ]. Previous evidence [ 29 ] suggests that severe hypertension can precipitate the onset of alveolar bleeding. When catecholamines rise, they mostly act on α-adrenergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic heart failure increases pulmonary venous pressure, which might induce micro-vessel rupture, resulting in DAH ( 13 , 14 ). Interestingly, a recent study showed that cardiovascular diseases increased long-term mortality in patients with DAH ( 15 ), which is indicative of a close pathophysiologic relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…Renin, aldosterone, vasopressin, catecholamines and endothelin might be involved in the alveolar-capillary injury. Finally, the bronchopulmonary arteries might have suffered directly from severe systemic hypertension in some patients as the bronchopulmonary arteries derive their blood supply from the systemic and pulmonary circulations or alveolar septal vessels [6].…”
Section: Blood Pressure On Admission Treatmentmentioning
confidence: 99%